Increased Risk of Kawasaki Disease in Infants Born of Mothers With Immune Disorders - Chu, Hsiao-Wen; Lin, Chien-Heng; Lin, Ming-Chih; Hsu, Ya-Chi (Frontiers in Pediatrics, 2021)
Introduction: Genetic susceptibility and immune dysregulation play important roles in the pathogenesis of Kawasaki disease (KD). However, it is still unclear whether KD causes immune disorder later in life or inherited susceptibility toward immune disorders causes KD. The aim of this study was to elucidate whether inherited immune disease properties from mothers increase the risk of KD from a population-based perspective. Method: Taiwan’s National Health Insurance Research Database was the main data source in this study. Parents and children were linked using the Taiwan Maternal and Child Health Database. Patients diagnosed with KD and younger than 18 years from 2004 to 2015 were enrolled as the study population. The control group was randomly selected from individuals without the diagnosis of KD matched by age, index year, sex, and urbanization level at a ratio of 1 to 10. The prevalence of maternal autoimmune and allergic diseases was compared between groups. Results: In total, 7178 children were found to have been diagnosed with Kawasaki disease. Then 71,780 children matched by index year, gender, and urbanization were randomly selected to serve as the control group. Children born from mothers with asthma and allergic rhinitis had a higher risk for developing KD. Children of mothers with an autoimmune disorder had a significantly increased tendency to develop KD. Maternal numbers of autoimmune disorders showed a dose-dependent relationship with KD incidence. Conclusion: This is the first population-based study to investigate maternal immune diseases and the risk of KD in their children. Children of mothers with immune disorders tend to have a higher risk of KD.